2019
DOI: 10.1111/jcpp.13043
|View full text |Cite
|
Sign up to set email alerts
|

Birth weight, verbal cognition in early adolescence, and lexical and reading skills in late adolescence: a formal mediation analysis using a potential outcomes approach

Abstract: Background: Oral and written language in late adolescence are influenced by many pre-and postnatal factors, including cognitive performance at earlier ages. We investigated whether the association between birth weight and lexical knowledge and reading comprehension in late adolescence (14-16 years) is mediated by verbal cognition during early adolescence (10-11 years). Methods: We conducted a mediation analysis via a potential outcomes approach to data from three United Kingdom (UK) prospective birth cohorts -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…As understanding and methods evolve, new opportunities to prevent what Virchow termed "artificial" conditions are the topics of ongoing research, particularly through longitudinal studies. Examples include the effects of birth weight, nursery care, family mental health, and social class on adult outcomes (3)(4)(5)(6)(7)(8)(9)(10). The conventional paradigm is to analyze the data and document correlations between characteristics, exposures, and outcomes, although identification of combinations of factors and use of specific statistical methods can result in better curve fitting (4).…”
Section: Introductionmentioning
confidence: 99%
“…As understanding and methods evolve, new opportunities to prevent what Virchow termed "artificial" conditions are the topics of ongoing research, particularly through longitudinal studies. Examples include the effects of birth weight, nursery care, family mental health, and social class on adult outcomes (3)(4)(5)(6)(7)(8)(9)(10). The conventional paradigm is to analyze the data and document correlations between characteristics, exposures, and outcomes, although identification of combinations of factors and use of specific statistical methods can result in better curve fitting (4).…”
Section: Introductionmentioning
confidence: 99%
“…Using the UK national cohorts, da Silva et al. 's () analyses showed that low birth weight (LBW; <2.5 kg) effects extend well into late adolescence (age 16) and durably impact oral and language skills as measured by lexical knowledge and reading comprehension. Mediation models indicated that indirect effects on verbal cognition during early adolescence (age 10) were stronger than the direct effects of LBW on adolescent reading comprehension.…”
mentioning
confidence: 99%